Anthocyanins Stability, Antioxidatie Activities, Antidepressant And Cytotoxicity Of Carissa Carandas Syrup: Effects Of Copigmentation Reaction. - Yusof, Siti Rafidah (2006)
In the present study, an attempt has been made to achieve anthocyanins stability and colour retention through copigmentation reaction. Ten copigments were added separately to pasteurized syrup (56 Brix), which was prepared from the ripe fruits of Carissa Carandas.